Tunable V-Cavity Laser with Butt-Joint Passive Tuning Section for Fast Wavelength Switching - Xiaolu Liao; Jia Guo; Jian-Jun He (IEEE Photonics Journal)
We report on the fast carrier-induced wavelength switching in V-cavity laser using butt-joint passive tuning section. Using the carrier plasma based tuning effect in combination with temperature induced gain spectrum shift, over 25-nm wavelength tuning with 100 GHz channel spacing is obtained with side-mode suppression ratio up to 40 dB. Sixteen channels can be switched by using a single electrode control on the long cavity electrode and seven channels on the short cavity electrode. Mode competition is observed during the transient and the switching delay time varies from 1 to 11 ns for different switching paths.